2017
DOI: 10.1039/c7py01179b
|View full text |Cite
|
Sign up to set email alerts
|

Construction of polymer coated core–shell magnetic mesoporous silica nanoparticles with triple responsive drug delivery

Abstract: Multi-responsive drug delivery systems are playing a very important role in nanomedicine, as they can feature as smart carriers releasing their payload on demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 69 publications
0
31
0
3
Order By: Relevance
“…However, this difference was not remarkable in the case of pH 5.5 [96]. Hegazy et al [97] reported a triple stimuli-responsive drug delivery system based on mesoporous silica and iron oxide nanoparticles. They used iron oxide (Fe 3 O 4 ) nanoparticles as a core with mesoporous silica coating loaded with ICG and DOX and functionalized with thermoresponsive PNIPAAM through disulfide linker.…”
Section: Dual/multi-responsive Ddsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this difference was not remarkable in the case of pH 5.5 [96]. Hegazy et al [97] reported a triple stimuli-responsive drug delivery system based on mesoporous silica and iron oxide nanoparticles. They used iron oxide (Fe 3 O 4 ) nanoparticles as a core with mesoporous silica coating loaded with ICG and DOX and functionalized with thermoresponsive PNIPAAM through disulfide linker.…”
Section: Dual/multi-responsive Ddsmentioning
confidence: 99%
“…They used iron oxide (Fe 3 O 4 ) nanoparticles as a core with mesoporous silica coating loaded with ICG and DOX and functionalized with thermoresponsive PNIPAAM through disulfide linker. Nanoparticles showed higher drug release at a higher temperature and in the presence of a reducing agent, tris(2-carboxyethyl) phosphine (TCEP) [97].…”
Section: Dual/multi-responsive Ddsmentioning
confidence: 99%
“…Multi-responsive nanocarriers that are sensitive to temperature and redox potential can effectively release their drug payload in the tumor microenvironment. Hegazy et al reported magnetic mesoporous silica nanoparticles (MMSNPs) that have iron oxide nanoparticles as a core inside a mesoporous silica coating [ 99 ]. They can be used in a wide range of disciplines and provide promising results.…”
Section: Multi-responsive Systemsmentioning
confidence: 99%
“…Other results indicated that both a magnetic field and a high temperature enhanced DOX release over time and reached 86% after 24 h, applying reducing potential and temperature together resulted in an 80% release. In summary, simultaneously applying thermal, redox potential, and magnetic-sensitive environments significantly improved the drug release from PNIPAAm/DOx NPs that reached 98% within 24 h [ 99 ]. The amount of drug release triggered by a random combination of two or three stimuli was higher than that mediated by any of the stimuli separately.…”
Section: Multi-responsive Systemsmentioning
confidence: 99%
“…Currently, the construction of single (functional) layer of shell is well established [6][7][8][9][10]. On the other hand, multiple layers of shells have to be elaborated for multiple extraneous functions [22][23][24][25]. The introduction of multiple shells, however, makes the preparation complicated and time consuming.…”
Section: Introductionmentioning
confidence: 99%